Sinergitas Antara Pemerintah Dengan Masyarakat Dalam Meningkatkan Pemberdayaan Ekonomi Masyarakat Melalui Badan Usaha Milik Desa (BUMDES) Di Kecamatan Talaga Jaya Kabupaten Gorontalo - Melis Ali; Andi Mardiana (MUTAWAZIN (Jurnal Ekonomi Syariah), 2022)
This study aims to find out how the synergy between the government and the community in icreasing community economic empowerment through BUMDES in Talaga Jaya Distric, Gorontalo Regency. This study is a qualitative research. Result of this sudy found that: 1) Synergy between stakeholders has been established with the process of social interaction because of a sense of trust, ownership, effective communication, creativity and innovation so as to form collaboration by individuals, groups, or organizations at the level community and have a common interest so that there is a good relationship for improving the community’s economy, 2) Training and providing business capital are efforts made to improve community economic empowerment, 3) There are still obstacles in the management of BUMDES, namely institutional management which is still not going well such as the lack of managerial ability in managing business so that in carrying out the program it does not get results that can improve the walfare of the community government.